The Effect of Total Work-Time Information on a Performance Evaluation Bias against Telecommuting Mothers - Wang, Laura W.; Williamson, Michael G.; Yang, Li (The Accounting Review, 2025)
ABSTRACT Organizations are increasingly utilizing remote monitoring tools that can track the total time telecommuting employees spend on work activities. We examine whether and how this information can eliminate a specific gender-based bias in the performance evaluations of telecommuting parents. Specifically, managers tend to evaluate telecommuting mothers less favorably than telecommuting fathers when performance outcomes are unfavorable, due to biased effort attribution. The availability of total work-time information can effectively eliminate this bias. Results from our main experiment and four supplemental experiments support our predictions and provide process-level evidence for our theory. Our theory and results suggest that leveraging remote monitoring tools’ capacity to track employees’ total work time can enhance the fairness and effectiveness of performance evaluations for telecommuting mothers.